2021
DOI: 10.1111/cea.13866
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to peanut, egg or pets is associated with skin barrier dysfunction in children with atopic dermatitis

Abstract: Background: Children with atopic dermatitis (AD) are often sensitized to food and aeroallergens, but sensitization patterns have not been analysed with biologic measures of disease pathogenicity. Objective:We sought to define allergen sensitization grouping(s) using unbiased machine learning and determine their associations with skin filaggrin (FLG) and transepidermal water loss (TEWL) (assesses skin barrier integrity), S100A8 and S100A9 expression (assesses skin inflammation) and AD severity. Methods:We studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
3
14
0
1
Order By: Relevance
“…As the levels of serum total IgE and age‐adjusted IgE have been correlated directly with AD severity, 9 it is likely that AD inflammation, rather than just skin infection, contributes to the increase in IgE. There is now increasing evidence that IgE sensitization occurs at the skin level in AD 10 . Due to barrier defects, environmental triggers including food allergens, aeroallergens, and S. aureus are capable of triggering AD inflammation, leading to the production of IgE.…”
Section: Discussionmentioning
confidence: 99%
“…As the levels of serum total IgE and age‐adjusted IgE have been correlated directly with AD severity, 9 it is likely that AD inflammation, rather than just skin infection, contributes to the increase in IgE. There is now increasing evidence that IgE sensitization occurs at the skin level in AD 10 . Due to barrier defects, environmental triggers including food allergens, aeroallergens, and S. aureus are capable of triggering AD inflammation, leading to the production of IgE.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 400 children with AD from the Mechanisms of Progression from Atopic Dermatitis to Asthma in Children cohort found that the most common SPT + allergens were egg white, followed by peanut, egg yolk, dog, trees, cat, ragweed, cockroach, mold, dust mite, grass, milk, weeds, soy, and wheat. 18 Children with AD and sensitization to peanut, egg, cat, and dog had a greater baseline skin barrier dysfunction (increased transepidermal water loss and decreased skin FLG expression) in nonlesional skin and AD severity than those with allergy to other allergens or no allergen sensitization. 18 Peanut and egg sensitization may occur through skin exposure in children.…”
Section: Epidemiology Of Fa In Admentioning
confidence: 94%
“… 18 Children with AD and sensitization to peanut, egg, cat, and dog had a greater baseline skin barrier dysfunction (increased transepidermal water loss and decreased skin FLG expression) in nonlesional skin and AD severity than those with allergy to other allergens or no allergen sensitization. 18 Peanut and egg sensitization may occur through skin exposure in children. 19 , 20 , 21 , 22 , 23 Individuals with AD are more likely to develop peanut sensitizations through skin exposure.…”
Section: Epidemiology Of Fa In Admentioning
confidence: 94%
“…increased TEWL and decreased FLG expression), and more severe disease (SCORAD) was observed in AD subjects who were poly-sensitized (specifically to peanut, egg, cat or dog) than children with no AD or with AD and other allergen sensitizations. 121 Another study found that pediatric AD patients with FA have greater skin barrier abnormalities (increased TEWL, reduced FLG breakdown products and reduced CER [EOS], esterified ω-hydroxy fatty acid sphingosine ceramides/CER [NS], non-hydroxy fatty acid sphingosine ceramides, ratio) as compared to AD without FA or non-AD controls. 122 …”
Section: What Is Known About Epidermal Abnormality In Ad?mentioning
confidence: 99%